2022
DOI: 10.1111/ijfs.15649
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐assisted catalytic synthesis of phytosterol esters

Abstract: A low‐temperature reaction is of considerable importance in avoiding the degradation of phytosterol esters caused by high temperatures. In this study, an efficient method under mild conditions was developed to synthesise phytosterol esters by using microwave‐assisted catalyst dodecyl benzene sulphonic acid (DBSA). The phytosterol conversion reached 94.27% under the optimal conditions: oleic acid to phytosterol molar ratio of 2.5:1, catalyst dosage of 20% (mol%) and reaction temperature of 60°C for 60 min. Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, in the absence of the catalyst, a large amount of excess fatty acids and high temperatures (≥180 °C) are needed to promote the reaction [ 11 , 34 ]. Moreover, in the catalytic experiment using a surfactant catalyst, dodecyl benzene sulphonic acid (DBSA), with different heating modes, a large number of catalysts (20 mol% of phytosterols) and complex postseparation processes are required [ 36 , 37 ]. Moreover, although acidic ionic liquids can also catalyze the esterification of phytosterol efficiently, the high catalyst dosage and high reaction temperature still restrict its large-scale application [ 13 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, in the absence of the catalyst, a large amount of excess fatty acids and high temperatures (≥180 °C) are needed to promote the reaction [ 11 , 34 ]. Moreover, in the catalytic experiment using a surfactant catalyst, dodecyl benzene sulphonic acid (DBSA), with different heating modes, a large number of catalysts (20 mol% of phytosterols) and complex postseparation processes are required [ 36 , 37 ]. Moreover, although acidic ionic liquids can also catalyze the esterification of phytosterol efficiently, the high catalyst dosage and high reaction temperature still restrict its large-scale application [ 13 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Zhang et al . reported that dodecyl benzene sulphonic acid (DBSA) assisted by microwave could efficiently promote this reaction, but a large amount of catalyst (20 mol% of phytosterols) was used and any side reactions were not analyzed 39 . In addition, when IL catalyst is used, the reaction temperature is relatively lower and a lighter color product with better quality can be obtained.…”
Section: Resultsmentioning
confidence: 99%
“…38 Recently, Zhang et al reported that dodecyl benzene sulphonic acid (DBSA) assisted by microwave could efficiently promote this reaction, but a large amount of catalyst (20 mol% of phytosterols) was used and any side reactions were not analyzed. 39 In addition, when IL catalyst is used, the reaction temperature is relatively lower and a lighter color product with better quality can be obtained. Based on these comparisons, compared with the catalysts reported in the literature, SO 3 H-functionalized IL catalyst [BSO 3 HMIm]Ts showed the advantages of high catalytic activity and selectivity in the synthesis of phytosterol ester.…”
Section: Comparison With Methods Used In Other Studiesmentioning
confidence: 99%